Arbuscular mycorrhizal fungi reduce growth and infect roots of the non‐host plant Arabidopsis thaliana - VEIGA, RITA S. L.; FACCIO, ANTONELLA; GENRE, ANDREA; PIETERSE, CORNÉ M. J.; BONFANTE, PAOLA; HEIJDEN, MARCEL G. A. (Plant, cell and environment, 2013)
The arbuscular mycorrhizal (AM) symbiosis is widespread throughout the plant kingdom but most terrestrial ecosystems also contain a considerable number of non‐mycorrhizal plants. The interaction of such non‐host plants with AM fungi is still poorly understood. In this study, we investigated whether the non‐mycorrhizal plant Arabidopsis thaliana, the model organism for plant molecular biology and genetics, interacts with AM fungi. We demonstrate, for the first time, that the presence of fungal networks formed by the AM fungus Rhizophagus irregularis reduces A. thaliana growth by 50% or more. In addition, by using bright field, confocal and electronic microscopy we show that this fungus can colonize roots of A. thaliana, although arbuscules were never observed. These results reveal high susceptibility of A. thaliana to R. irregularis, suggesting that A. thaliana is a suitable model plant to study non‐host/AM fungi interactions and the biological basis of AM incompatibility. Commentary: Interactions between arbuscular mycorrhizal and non‐mycorrhizal plants: do non‐mycorrhizal species at both extremes of nutrient‐availability play the same game? The arbuscular mycorrhizal (AM) symbiosis is widespread throughout the plant kingdom and important for plant nutrition and ecosystem functioning. Nonetheless, most terrestrial ecosystems also contain a considerable number of non‐mycorrhizal plants. The interaction of such non‐host plants with AM fungi (AMF) is still poorly understood. Here, in three complementary experiments, we investigated whether the non‐mycorrhizal plant Arabidopsis thaliana, the model organism for plant molecular biology and genetics, interacts with AMF. We grew A. thaliana alone or together with a mycorrhizal host species (either Trifolium pratense or Lolium multiflorum) in the presence or absence of the AMF Rhizophagus irregularis. Plants were grown in a dual‐compartment system with a hyphal mesh separating roots of A. thaliana from roots of the host species, avoiding direct root competition. The host plants in the system ensured the presence of an active AM fungal network. AM fungal networks caused growth depressions in A. thaliana of more than 50% which were not observed in the absence of host plants. Microscopy analyses revealed that R. irregularis supported by a host plant was capable of infecting A. thaliana root tissues (up to 43% of root length colonized), but no arbuscules were observed. The results reveal high susceptibility of A. thaliana to R. irregularis, suggesting that A. thaliana is a suitable model plant to study non‐host/AMF interactions and the biological basis of AM incompatibility.